Kings and queens at home: a short history of the chess column in 19th century English periodicals - HARDING, TIMOTHY DAVID (My University, 2009)
This article examines the origin and growth of chess columns in English periodicals. The space devoted by many magazines and newspapers to games and puzzles is a research topic that has mainly been ignored by scholars. Nowadays we are familiar with crosswords, sudoku, and bridge columns. Some Victorian periodicals printed brainteasers of various kinds, but between the 1850s and 1914 chess problems were the most common form of intellectual exercise in periodicals. Chess grew from a feature seen in a handful of titles at mid-century into one that was almost required reading in a weekly paper by the 1880s, sometimes as part of an ?amusements? package. The columns themselves were an important driver of growth for chess, showing examples of good play, offering advice of various kinds, and running competitions, as well as providing puzzles for readers to solve.
ACCEPTED
Keywords: Chess; English periodicals